(untitled) - Hudak, Anton; Vrabel, Jan (Doprava a spoje, 2010)
There are declared differences in using summer, winter and all-weather tyre application in the article. The article also contains analysis of tyre forces effecting, aquaplaning creation, consequences to breaking distance and whole affect to the road traffic safeness.